MRI‐Based Brain Structure Volumes in Temporal Lobe Epilepsy Patients and their Unaffected Siblings: A Preliminary Study. Issue 1 (28th August 2012) - Scanlon, Cathy; Ronan, Lisa; Doherty, Colin P.; Cavalleri, Gianpiero L.; Tirupati, Sandya; Alhusaini, Saud; Maguire, Sinead; Delanty, Norman; Iyer, Parameswaran M.; Chaila, Elijah; Fitzsimons, Mary
<x xml:space="preserve">Abstract</x> ABSTRACT INTRODUCTION Investigating the heritability of brain structure may be useful in simplifying complicated genetic studies in temporal lobe epilepsy (TLE). A preliminary study is presented to determine if volume deficits of candidate brain structures present at a higher rate in unaffected siblings than controls subjects. METHODS T1‐weighted MR images was acquired for 28 TLE patients, a same‐sex unaffected sibling of 12 of these and 28 normal controls. Selected brain structure volumes were measured using an automated whole brain segmentation technique. Candidate brain structure endophenotypes were determined and group differences were investigated between (1) controls and patients and (2) controls and siblings. ICC's were used to measure the quantitative volumetric association within each sibling pair. RESULTS TLE patients demonstrated a significantly lower cerebral white matter, bilateral hippocampus, thalamus, and left entorhinal cortex volumes when compared with controls. A significant deficit in cerebral white matter (CWM) was common to patient and nonaffected siblings when compared with controls. Furthermore, a significant correlation was revealed between patients and siblings in CWM and bilateral thalamus. CONCLUSION The findings suggest an overlap in the neurodevelopmental genes responsible for both brain structure and the expression of the disease. Further work is ongoing to confirm these findings.